L'institution du réalisme. Ce que les tensions de l'action publique font aux pratiques d'orientation des élèves allophones - Thomas Douniès (Les éditions de la Maison des sciences de l'Homme, 2023)
The discernment between the realistic and the unrealistic is a major mode of construction of orientation verdicts that this article proposes analyze throughout the impact on professional practices within the schools of public policy dynamics from inside and outside the education system. The study is based on the case of the post-third grade orientation of pupils of the UPE2A of a middle school located in a priority education zone. The analysis shows that the narrowing of school possibilities for the students makes sense in the way that professionals negotiate the tension between the institutional motto of schooling that must take place "like the others" and the real conditions of schooling that weaken its realization, from the difficult feasibility of the "inclusive" incentive to the constraints of extracurricular logics linked to the management of migrant populations outside school.